Modernization of Audit Process: Utilization of Technology on Evaluation of Audit Evidence - Ruslaini Ruslaini; Ngadi Permana; Yessica Amelia (Indonesian Economic Review, 2024)
This study aims to examine the impact of new technologies on audit evidence evaluation and the modernization of audit standards. With advancements in technology, particularly in artificial intelligence (AI), big data, and blockchain, the audit process has undergone significant changes in how evidence is collected, analyzed, and evaluated. These technologies enhance efficiency, accuracy, and transparency in audits, but also pose challenges in terms of auditor adaptation and the updating of audit standards. This literature review identifies that the use of AI and big data allows auditors to handle large volumes of data more quickly, while blockchain offers solutions to improve the security and integrity of audit evidence. Although the benefits are substantial, the implementation of new technologies requires regulatory updates, the development of auditors' technical skills, and adjustments to existing infrastructure. This study suggests the need for collaboration between auditors, regulators, and technology developers to ensure the appropriate and effective use of technology in auditing. The findings are expected to provide guidance for audit professionals and regulatory authorities in navigating the rapid changes in the auditing landscape.